COMMUNITY-BASED ENTREPRENEURSHIP EMPOWERMENT PROGRAM AND ITS ROLE IN WOMEN'S ECONOMIC INDEPENDENCE: A CASE STUDY IN BANYUMAS REGENCY - Fatwa Zuhanea (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Women's economic independence remains a persistent challenge in developing economies, particularly at the grassroots level. This study investigates the influence of community-based entrepreneurship empowerment programs on women's economic independence in Banyumas Regency, Central Java, Indonesia. Grounded in the Social Learning Theory of Bandura (1977) and the Resource-Based View (RBV), this research examines the mediating role of entrepreneurial skills acquisition and access to capital between program participation and economic independence. Using a quantitative approach with a cross-sectional survey, data were collected from 132 women participants of Kelompok Usaha Bersama (KUBE) programs in five sub-districts of Banyumas Regency. The results of Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis indicate that community-based empowerment programs significantly and positively influence women's economic independence (β = 0.431, p < 0.001). Entrepreneurial skills acquisition and access to capital partially mediate this relationship. The findings contribute both theoretical and practical insights into how grassroots-level empowerment programs can serve as effective tools for promoting gender-inclusive economic growth in rural settings.Keywords: community-based empowerment, women's economic independence, entrepreneurship program, KUBE, Banyumas Regency Keywords: community-based empowerment, women's economic independence, entrepreneurship program, KUBE, Banyumas Regency